Volba optimální právní formy podnikání - Leichmanová, Iveta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce se zabývá volbou optimální právní formy podnikání pro konkrétní podnikatelský subjekt. Specifikuje jednotlivá hodnotící kritéria, která by měla být zohledněna při výběru nejvhodnější formy podnikání. Tyto kritéria jsou dále hodnocena a srovnána vzhledem k vybraným formám podnikání. Komparací jednotlivých variant je vyhodnocena a vybrána nejvhodnější právní forma podnikání pro konkrétního podnikatele.

Bachelor´s thesis deals with the selection of optimal legal form for business activities for a particular company. It specifies individual evaluating criteria, whit should be taken into account in selection the most appropriate form of business. These criteria´s are further evaluated and compared within chosen forms of business. By comparison of individual variants they are evaluated and chosen for the most suitable legal form for specific businessman.
Selection of Optimal Legal Form for Business Activities
Keywords: formy podnikání; osoba samostatně výdělečně činná; společnost s ručením omezeným; daňová zátěž; sociální pojištění; zdravotní pojištění; forms of business organization; self-employed; limited liability Company; tax burden; social security insurance; health insurance